2005
DOI: 10.1111/j.1399-3046.2005.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy for hepatic artery thrombosis following liver transplantation: Current concepts

Abstract: This article presents the case of an infant who underwent an orthotopic liver transplant and then developed hepatic artery thrombosis that was detected on routine post-operative right upper quadrant ultrasound. Alteplase (TPA) failed to open the artery, so the child received systemic heparin and hyperbaric oxygen (HBO) therapy. After six HBO treatments, the hepatic artery had recanalized and his liver function tests had returned to normal or near normal. There were no complications to the HBO therapy, and 1 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…This strategy is frequently used in various diseases associated with impaired oxygen delivery [40,41]. While there are several experimental studies emphasizing the beneficial effects of HBO on assorted liver diseases [15][16][17][18][19][20][21], its use in clinical practice has been limited to small series of hepatic artery thrombosis [42][43][44] and miscellaneous cases of liver failure [45,46]. In addition, arguments on the utilization of HBO in an oncological framework concentrate on a possible Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is frequently used in various diseases associated with impaired oxygen delivery [40,41]. While there are several experimental studies emphasizing the beneficial effects of HBO on assorted liver diseases [15][16][17][18][19][20][21], its use in clinical practice has been limited to small series of hepatic artery thrombosis [42][43][44] and miscellaneous cases of liver failure [45,46]. In addition, arguments on the utilization of HBO in an oncological framework concentrate on a possible Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical liver transplant setting, the positive settings of HBO include the treatment of hepatic artery thrombosis for which surgery is not indicated. 110,111 We recently reported that preoperative HBO pretreatment had benefi cial effects in a rat model of massive hepatectomy, by protecting hepatocytes through the induction of heat shock proteins. 112…”
Section: Other Strategiesmentioning
confidence: 99%
“…Another important point in favor of HBO is the lower cost caused by the reduction of extensive medical and surgical care. The utilization of HBO in infants is only restricted to case reports in other specialities for instance for hepatic artery thrombosis following liver transplantation [15]. …”
Section: Discussionmentioning
confidence: 99%